2011
DOI: 10.2478/v10098-011-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Regression Models for Determining Water Retention Curves

Abstract: A key physical property used in the description of a soil-water regime is a soil water retention curve, which shows the relationship between the water content and the water potential of the soil. Pedotransfer functions are based on the supposed dependence of the soil water content on the available soil characteristics, e.g., on the relative content of the particle size in the soil and the dry bulk density of the soil. This dependence could be extracted from the available data by various regression methods. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Twarakavi et al () developed SVM‐based PTFs using the data set of Rosetta (Schaap et al, ) and found SVMs outperforming ANN‐based PTFs. More recent applications include Skalová et al (), Haghverdi et al (), Nguyen et al (), and Khlosi et al ().…”
Section: Methods To Derive and Evaluate Pedotransfer Functionsmentioning
confidence: 99%
“…Twarakavi et al () developed SVM‐based PTFs using the data set of Rosetta (Schaap et al, ) and found SVMs outperforming ANN‐based PTFs. More recent applications include Skalová et al (), Haghverdi et al (), Nguyen et al (), and Khlosi et al ().…”
Section: Methods To Derive and Evaluate Pedotransfer Functionsmentioning
confidence: 99%
“…15 compared the applicability of SWRCs using three major soil samples with different soil textures and from different geographical locations within Iran, indicating that the applicability of SWRCs varied owing to different soil texture. Therefore, model selection and comparison are prerequisite before the most suitable one can be determined for SWRCs of specific soils, and suchlike comparisons have been conducted 11,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on pedotransfer functions have been carried out by many authors (e.g. Trzecki 1974Trzecki , 1976Varallyay and Mironienko 1979, Van Genuchten 1980, Rawls and Brakensiek 1982, Varallyay et al 1982, Walczak 1984, Carsel and Parrish 1988, Wösten et al 1999, Vereecken et al 1989Schaap et al 2001, Pachepsky and Rawls 2004, Walczak et al 2004, Dexter et al 2008, Gnatowski et al 2006Guber and Pachepsky 2010, Skalova et al 2011, Puhlmann and von Wilpert 2012, Hewelke et al 2013Brogowski and Kwasowski 2015, Lamorski et al 2017, Oleszczuk et al 2018. Among the developed models, we can distinguish continuous functions, enabling the moisture content of soil (θ) to be calculated for any given matrix potential (h), as well as discontinuous functions, making it possible to indicate the θ(h) relationships for characteristic θ values.…”
Section: Introductionmentioning
confidence: 99%